Pengaruh Brand Awareness terhadap Consumer Decision Making - Rianty Ameliawaty; Ii Halilah (Jurnal Riset Bisnis dan Investasi, 2017)
This study to find out how brand awareness in CFC Bandung, how consumer purchasing decisions in CFC Bandung, and how the influence of brand awareness of purchasing decisions in CFC Bandung. This research is done by using quantitative method with descriptive data analysis. The number of samples in this study was 117 consumers who ever made a purchase in CFC Bandung. Test this instrument, reliability test, hypothesis test, simple regression. The results show that brand awareness has influence with 49% by having a significant positive relationship is very strong. Brand awareness has a simple linear regression value of 0.370. This means that brand awareness increases one unit, the consumer purchasing decisions will increase by 0.370 units. This study shows that brand awareness has an influence on consumer purchasing decision in CFC Bandung.